2015
DOI: 10.1097/aog.0000000000001156
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcomes by Attempted Mode of Operative Delivery From a Low Station in the Second Stage of Labor

Abstract: Objective To evaluate maternal and neonatal outcomes by attempted mode of operative delivery from a low station in the second stage of labor. Methods Retrospective study of 2,518 women carrying singleton fetuses at ≥37 weeks gestation who underwent attempted forceps-assisted delivery, attempted vacuum-assisted vaginal delivery, or cesarean delivery from a low station in the second stage of labor. Primary outcomes were stratified by parity and included a maternal adverse outcome composite (postpartum hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 19 publications
(28 reference statements)
5
45
3
1
Order By: Relevance
“…However, the procedure-related definition of increased blood loss leads to higher rates in instrumental delivery, even if the mean blood loss estimated in ml is higher in CS. These results are in contradiction to previous ones, as there were no significant differences for maternal hemorrhage [10,11] . Differently used cut-off definitions for high blood loss or hemorrhage within studies make comparisons of data difficult, as for example in one study a significant hemorrhage was defined as the need for blood transfusion [10] .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, the procedure-related definition of increased blood loss leads to higher rates in instrumental delivery, even if the mean blood loss estimated in ml is higher in CS. These results are in contradiction to previous ones, as there were no significant differences for maternal hemorrhage [10,11] . Differently used cut-off definitions for high blood loss or hemorrhage within studies make comparisons of data difficult, as for example in one study a significant hemorrhage was defined as the need for blood transfusion [10] .…”
Section: Discussioncontrasting
confidence: 56%
“…An earlier study described the highest rates of short-term neonatal and maternal complications after instrumental-assisted delivery compared to vaginal delivery and CS in labour [10] . However, a recent study presented contradictory results [11] showing no differences for maternal adverse outcome parameters, and even demonstrated a lower neonatal adverse outcome among nulliparous women who delivered forceps-assisted delivery [11] . Another study demonstrated that neonates born by CS in labour are also vulnerable to intracranial trauma [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that babies delivered by caesarean section (CS) have lower Apgar scores in comparison to those delivered vaginally [11] with a higher risk after emergency procedures.…”
Section: Introductionmentioning
confidence: 99%
“…6 The literature on perinatal and maternal mortality and morbidity after operative vaginal delivery compared with cesarean delivery is inconsistent. [7][8][9][10][11][12][13][14][15][16] In addition, studies on the risks and benefits of these Increased use of operative vaginal delivery (i.e., forceps or vacuum application), of which 20% occurs at midpelvic station, has been advocated to reduce the rate of cesarean delivery. We aimed to quantify severe perinatal and maternal morbidity and mortality associated with attempted midpelvic operative vaginal delivery.…”
mentioning
confidence: 99%